Effect of Profit Power, Term Commitment, Capital Structure, and Investment Opportunity on Earnings Quality - Gita Olyvia Olyvia Fachrunnisa*; Shinta Permata Sari (Universitas Syiah Kuala, 2023)
Currently the quality of earnings is a matter of great concern as an interesting issue to study related to accounting. Earnings quality and financial reporting quality are generally of concern to users of financial statements for contractual purposes and for making investment decisions. This study aims to examine the effect on earnings quality. The population in this study are manufacturing companies in the consumer goods sector that are listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The sample in this study was a manufacturing company which was determined by purposive sampling method, and obtained 73 companies as a sample. Analysis of research data using multiple linear regression. Data is processed using SPSS. The results show that capital structure and investment opportunities have an effect on earnings quality, while profit power and term commitment have no effect on earnings quality. This research can be used as an evaluation material for companies to improve the quality of their earnings.